Tax Avoidance dan Faktor Pemicunya: Bukti Meta-Analitik dari Studi-Studi Empiris - Dibah, Fara; Limba, Franco Benony (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to examine what dominant variables affect tax avoidance. There are also four (4) variables used in this study, namely variables, profitability, leverage, company size, and audit committee. The population in this study is journals contained in SINTA 2-4. The total sample used amounted to 50 journals for the period 2018-2022. The data analysis technique in this study is meta-analysis, and processed using JASP. The results of this study indicate that profitability, company size, and the audit committee do not affect tax avoidance, leverage affects tax avoidance. So that the variable that has a dominant effect is leverage, because leverage is the only variable that affects tax avoidance compared to the other three variables.